Marchas e contramarchas no financiamento público da saúde: reflexões a partir do arranjo normativo brasileiro - Laura Monteiro de Castro Moreira (2018)
Among the critical areas of a health system, financing stands out among those of greater relevance and complexity. In the Brazilian case, the current setbacks to social security reinforce the need to bring to the debate this vital issue to guarantee the right to health. This paper aims to understand the configuration of public financing of the Sistema Único de Saúde (SUS) according to the rules that regulates the dynamics of transfer and allocation of resources among federated entities. Its construction was based on practical issues that occupied the agenda during its elaboration. When designing, Ordinance no. 4,279/10 and Decree no. 7,508/11 were among the normative efforts to overcome fragmentation and improve the political-institutional functioning of SUS. A case study was developed to understand the federal funding of medium and high complexity hospital and outpatient care (MAC) and its relation with the implementation of the guidelines proposed by these regulations within the SUS of Minas Gerais state. Decentralization of responsibilities, resources and new forms of financing was verified, which contributed to the expansion of the network model in the state. The amount of resources transfered preseted by the federal government refers to the debate between national coordination versus autonomy and locoregional solutions. In view of the findings and the review scenario of Administrative Rule no. 204/07, with changes in the organization of federal transfers, the public health financing was analyzed based on the revenues and expenditures reported by the federated entities to the Information System on Public Budgets in Health (SIOPS) in the period 2007 to The total and per capita values available for the SUS in all groups of regions, increased participation of basic health care, increased investment in regions with a lower supply capacity, and increased proportional participation of own resources. The volatility of the regulation on public health financing has not contributed to the effective implementation of SUS, and the observed movements suggest a risk to the strategy of organization of the health system oriented by primary care, compromising the guarantee of integral and quality assistance.